PENDEKATAN SCIENCE, TECHNOLOGY, ENGINEERING AND MATHEMATICS DALAM PEMBELAJARAN KIMIA 4.0 - Losarini Sumartati (Balai Diklat Keagamaan Bandung, 2020)
In the era of the industrial revolution 4.0, teachers are required to be able to carry out creative and innovative learning by utilizing technology. One approach that fits these demands is the STEM (Science, Technology, Engineering and Mathematics) approach. The purpose of this paper is to describe the STEM concept and the implementation of the STEM approach to Chemistry learning at the Madrasah Aliyah / Senior High School level. The method used in this writing is literature review by selecting several articles and journals regarding the STEM approach and its implementation at Madrasah Aliyah / Senior High School level. In addition, a basic competency study of 2013 curriculum was conducted which could be integrated into the STEM approach. The results of the study show that some of the basic competencies in Chemistry subjects in Madrasah Aliyah / Senior High Schools can be integrated with the STEM approach through the stages of the STEM approach and giving projects to students. In this way, the implementation of the STEM approach in the Chemistry subject of Madrasah Aliyah / Senior High School can be done in order to prepare competent human resources to face the 21st century.